Patient Safety: The Implementation of Patient Identification in the New Normal - Sri Hananto Ponco Nugroho; Puguh Widiyanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Identifying errors at the beginning of the service will have an impact on the errors at the next stage. Nurses have a central role in safe drug delivery. This study aimed to determine the implementation of patient identification. The research used descriptive analytic with a cross-sectional approach. A total of 134 nurses was selected to be the samples trough purposive sampling at a hospital in Temanggung Regency. The data were collected using questionnaires and observation sheets. The data were analyzed using a frequency distribution. The results showed that the application of patient identification was categorized as low (less than 100%). Nurses need to improve the implementation of patient identification according to standards so that it will improve the quality of services that focus on patient safety. Abstrak: Kesalahan identifikasi diawal pelayanan akan berdampak pada kesalahan pelayanan tahap berikutnya. Perawat memiliki peran sentral dalam pemberian obat yang aman. Penelitian ini bertujuan mengetahui penerapan identifikasi pasien. Desain penelitian yang digunakan adalah deskriptif analitik dengan pendekatan cross sectional. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel sebanyak 134 perawat di sebuah rumah sakit di Kabupaten Temanggung. Pengambilan data menggunakan kuesioner dan lembar observasi. Data dianalisis menggunaan distribusi frekuensi. Hasil penelitian menunjukkan bahwa penerapan identifikasi pasien dikategorikan rendah (kurang dari 100%). Perawat perlu meningkatkan penerapan identifikasi pasien yang sesuai stadar sehingga akan meningkatkan kualitas layanan yang berfokus pada keselamatan pasien.